Ganti Rugi Korban Terorisme Ditinjau dari Perspektif Sosio-Legal - Fazal Akmal Musyarri (Jurnal Hukum Lex Generalis, 2020)
Acts of terrorism is a form of real crime that has been in the spotlight for some time. In fact, at the end of 2020, found traces of kingpins that allegedly constituted terrorism training in west Java. This encourages not only the study of the crime of terrorism but also the need to think about the fate of people who are victims of terrorism crimes as an Extra Ordinary Crime. Terrorism is said to be very evil because of its organized nature and can cause casualties, physical injuries, to losses both materially and non-materially. This is what needs to be discussed also in a legal perspective. Not only in terms of normative because basically, the arrangement regarding compensation for victims of terrorism still raises question marks in the condition of the perpetrator who died or has not been found syndication responsible for acts of terrorism. Therefore, in this paper will be discussed about the compensation of victims of terrorism not only from a normative but also socio-legal view.